Gait and Function in Class III Obesity. (16th February 2012) - Ling, Catherine; Kelechi, Teresa; Mueller, Martina; Brotherton, Sandra; Smith, Sheila
Abstract : Walking, more specifically gait, is an essential component of daily living. Walking is a very different activity for individuals with a Body Mass Index (BMI) of 40 or more (Class III obesity) compared with those who are overweight or obese with a BMI between 26–35. Yet all obesity weight classes receive the same physical activity guidelines and recommendations. This observational study examined the components of function and disability in a group with Class III obesity and a group that is overweight or has Class I obesity. Significant differences were found between the groups in the areas of gait, body size, health condition, and activity capacity and participation. The Timed Up and Go test, gait velocity, hip circumference, and stance width appear to be most predictive of activity capacity as observed during gait assessment. The findings indicate that Class III-related gait is pathologic and not a normal adaptation.